(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article makes an attempt to present the philosophical nature of I. Annensky’s lyrics. He uses poetic form to express philosophical thoughts and reflect sentiments related to human reality and the meaning of life.